The Development of the Tax Expenditures in Turkey: 2015-2021 - Recep Emre Eriçok (İstanbul İktisat Dergisi)
Nowadays, tax expenditures are extensively applied in many countries in order to achieve certain economic and social goals more effectively and quickly. Tax expenditures generally represent forgone tax revenues and in practice they appear in the form of tax exemptions and exceptions, reductions, credits, low tax ratios and tax deferrals. Tax expenditures, which are practices that lead to tax loss in terms of the public economy, are also considered as a kind of public expenditures. Therefore, the effective implementation of tax expenditures in the public economy is important in terms of income and expenditure policies. In this study, prepared in order to analyse the development of tax expenditures in Turkey, first the concept of tax expenditures and the theoretical framework and implementations were examined, then the volume of tax expenditures, increase ratios, distribution according to the categories of taxes, and ratios to various macro indicators were analysed, using the estimated tax expenditures of the 2015-2021 period in Turkey. Then, the functional distribution of tax expenditures were covered and it was determined which areas these expenditures are directed towards. Finally, the ratio of tax expenditures in Gross Domestic Product in various countries was examined and an attempt to determine the situation in Turkey was made. The results of the study show that tax expenditures are extensively applied in Turkey especially in recent years, as an active fiscal policy tool besides the other policy measures, in order to revive the economy. Furthermore, it is envisaged that tax expenditures will contribute positively to the economic performance of Turkey by means of increasing efficiency and effectiveness and providing fiscal transparency in tax expenditures.